Testing and Monitoring of the First Timber Bridge for Road Traffic in Korea - Yi, Jiwoon; Park, Jang Ho; Park, Wonsuk; Kim, Chul Ki; Choo, Jinkyo F. (KSCE Journal of Civil Engineering, 2021)
Compared to steel and concrete, wood offers a fully renewable construction material with lesser carbon footprint and high strength-to-weight ratio. However, this material has become relatively unknown and ignored in the civil engineering community apart from cosmetic purpose. This study intends to provide insight on the design of a timber bridge for road traffic and presents the results of a series of full-scale laboratory test and monitoring performed conducted on Hanareum bridge, the first timber bridge for road traffic constructed in Korea. The arched truss bridge is made of glulam and spans over 30 m with two traffic lanes for a width of 8.4 m. The laboratory test considered tensile, compressive as well as bending tests on full-scale members, connections and the entire superstructure. Truck load testing involved both static and dynamic loading from which the dynamic properties and behavior of the bridge could be assessed. Finally, regular monitoring enabled to observe eventual seasonal variation of wood. The analysis of the results show that the structure continues to behave elastically as desired, that the maximum deflection at mid-span reaches merely 24% of the allowable deflection, and that the stress level remains far below the allowances even after 6 years of operation.
Keywords: Dynamic property; Engineering community; Laboratory test; Maximum deflection; Seasonal variation; Static and dynamic loading; Stress levels; Traffic lanes; Arched truss; Glulam; Long-term monitoring; Timber bridge; Truck loading test